A single spark - Miller, Judith, 1944- (Bethany House Publishers, 2020)
"Wanting to do her part in the war effort, Clara McBride goes to work in the cartridge room at the Washington Arsenal, the city's main site for production and storing of munitions. She's given the opportunity to train new employees and forms a friendship with two of them. All seems to be going well, especially when one of the supervisors shows interest in her. Lieutenant Joseph Brady is an injured army officer who, no longer able to lead troops into battle, has been assigned to a supervisory position at the Washington Arsenal. While Clara has caught his eye, he also makes it his mission to fight for increased measures to prevent explosions in the factory. But when suspicions rise after multiple shipments of Washington Arsenal cartridges fail to fire and everyone is suspect for sabotage, can the spark of love between Joseph and Clara survive?"--